1998
DOI: 10.1097/00007691-199804000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Concentrations of Melatonin in Saliva and Serum in Patients With Delayed Sleep Phase Syndrome

Abstract: Exogenous melatonin, which can be used to treat certain circadian rhythm disorders, maximally advances delayed rhythms when administered 5 hours before the endogenous melatonin starts to increase. The time of the start of the endogenously melatonin is defined as Dim Light Melatonin Onset (DLMO). The DLMO concentration has been defined in serum to be 10 pg/ml. Because of the greater practicability of frequent saliva sampling over blood sampling, we have validated radioimmunoassay (RIA) measurements of melatonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 3 publications
2
51
0
Order By: Relevance
“…Our results demonstrate a blockage in both diurnal and nocturnal production of melatonin in CRF, which generates a lack of rhythmicity in the content of this hormone. The salivary melatonin content of the control group at night during the beginning of sleep was 5.9 pg/ml, which is in agreement with previous studies that reported a normal salivary melatonin content of 4 pg/ml for this period [25]. When salivary Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Our results demonstrate a blockage in both diurnal and nocturnal production of melatonin in CRF, which generates a lack of rhythmicity in the content of this hormone. The salivary melatonin content of the control group at night during the beginning of sleep was 5.9 pg/ml, which is in agreement with previous studies that reported a normal salivary melatonin content of 4 pg/ml for this period [25]. When salivary Fig.…”
Section: Discussionsupporting
confidence: 91%
“…In these, melatonin output is normal but not synchronized with the external day-night variations [26]. The temperature-lowering effects of melatonin seem to occur later than sleep induction and may therefore not be the cause for the sleeppromoting effects of melatonin [27].…”
Section: Introductionmentioning
confidence: 95%
“…4 These effects are distinct from those that result from the introduction of supraphysiological amounts of melatonin from exogenous sources, some of which are not receptor-mediated and involve metabolism, either in terms of formation of new bioactive compounds or interactions with free radicals. 1,2 Melatonin has been used successfully in the treatment of insomnia in older individuals, [5][6][7] in circadian rhythm sleep disorders-in particular, delayed sleep phase syndrome [8][9][10] -and in sleep disorders in children with various neurologic diseases. [11][12][13] Studies of the effects of melatonin on decreasing sleep latency and on total sleep have not always produced consistent results, however, with some investigators reporting an absence of effects.…”
Section: Introductionmentioning
confidence: 99%